Overexpression of Toll-Like Receptor 4 Affects Autophagy, Oxidative Stress, and Inflammatory Responses in Monocytes of Transgenic Sheep - Wang, Sutian; Song, Xuting; Zhang, Kunli; Deng, Shoulong; Jiao, Peixin; Qi, Meiyu; Lian, Zhengxing; Yao, Yuchang (Frontiers in Cell and Developmental Biology, 2020)
Toll-like receptor 4 (TLR4) is a critical pattern recognition receptor that plays a critical role in the host innate immune system’s recognition of Gram-negative bacteria. Since it is the lipopolysaccharide (LPS) receptor, it links the activated inflammatory response with autophagy and oxidative stress. Autophagy, or type II programmed cell death, was reported to have defensive functions in response to the production of inflammatory cytokines and oxidative stress. To explore the relationship between autophagy, inflammation, and oxidative stress, a TLR4-enriched transgenic animal (Tg) model (sheep) was generated. Autophagy activity in the Tg blood monocytes was significantly higher than in the wild-type animal under LPS stress and it returned to normal after transfection of TLR4 siRNA. Pretreatment with 3-methyladenine (3-MA) inhibited autophagy and enhanced oxidative stress and the production of TNF-α. The LPS-induced reactive oxygen species (ROS) level was markedly increased in the Tg group at an early stage, before quickly returning to normal values. In addition, suppressing ROS production by N-acetyl-L-cysteine (NAC) down-regulated the number of intracellular autophagosomes, and the expression of Beclin-1, ATG5 and cytokines IL-1β, IL-6, and TNF-α. Further mechanistic investigation suggested that the TLR4-associated p38 mitogen-activated protein kinase (MAPK) signaling pathway was involved in autophagy and oxidative stress. P38 MAPK promotes intracellular autophagy, ROS production and the inflammatory response. Moreover, TLR4 over-expression suppressed oxidative stress and the production of inflammatory cytokines and increased autophagy activity in vivo. Taken together, our results showed that LPS induced autophagy, which was related to TLR4-mediated ROS production through the p38 MAPK signaling pathway. In addition, our study also provided a novel transgenic animal model to analyze the effects of TLR4 on autophagy, oxidative stress and inflammatory responses.